(untitled) (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Potato (Solanum tuberosum L.) is an economically and nutritionally relevant crop in the Andean region of Ecuador, whose yield has been affected by the frequency and intensity of frosts that damage tissues and reduce productivity. In this work, the role of salicylic acid (SA) as a biostimulant in in vitro potato microtubers of the cultivar Diacol Capiro grown under cold conditions was evaluated. Microtubers were established in supplemented MS medium and subjected to four contrasting treatments of temperature and SA. Preliminary results showed successful in vitro culture establishment as well as successful microtuber formation. On the other hand, SA is expected to promote protective physiological responses against frost, and metabolomic analysis will complement these findings by identifying differential compounds associated with cold tolerance.